Open Lung in Lateral Decubitus With Differential Selective Positive End-Expiratory Pressure in an Experimental Model of Early Acute Respiratory Distress Syndrome*. Issue 10 (October 2015) - Borges, João Batista; Senturk, Mert; Ahlgren, Oskar; Hedenstierna, Göran; Larsson, Anders
Abstract : Objective: After lung recruitment, lateral decubitus and differential lung ventilation may enable the titration and application of optimum-selective positive end-expiratory pressure values for the dependent and nondependent lungs. We aimed at compare the effects of optimum-selective positive end-expiratory pressure with optimum global positive end-expiratory pressure on regional collapse and aeration distribution in an experimental model of acute respiratory distress syndrome. Design: Prospective laboratory investigation. Setting: University animal research laboratory. Subjects: Seven piglets. Interventions: A one-hit injury acute respiratory distress syndrome model was established by repeated lung lavages. After replacing the tracheal tube by a double-lumen one, we initiated lateral decubitus and differential ventilation. After maximum-recruitment maneuver, decremental positive end-expiratory pressure titration was performed. The positive end-expiratory pressure corresponding to maximum dynamic compliance was defined globally (optimum global positive end-expiratory pressure) and for each individual lung (optimum-selective positive end-expiratory pressure). After new maximum-recruitment maneuver, two steps were performed in randomized order (15 min each): ventilation applying the optimum global positive end-expiratory pressure and the optimum-selective positive end-expiratory pressure. CT scans were acquired at end expiration and end inspiration. Measurements and Main Results: Aeration homogeneity was evaluated as a nondependent/dependent ratio (percent of total gas content in upper lung/percent of total gas content in lower lung) and tidal recruitment as the difference in the percent mass of nonaerated tissue between expiration and inspiration. At the end of the 15-minute optimum-selective positive end-expiratory pressure, compared with the optimum global positive end-expiratory pressure, resulted in 1) decrease in the percent mass of collapse in the lower lung at expiratory CT (19% ± 15% vs 4% ± 5%; p = 0.03); 2) decrease in the nondependent/dependent ratio between the optimum global positive end-expiratory pressure-expiratory-CT and optimum-selective positive end-expiratory pressure-expiratory-CT (3.7 ± 1.2 vs 0.8 ± 0.5; p = 0.01); 3) decrease in the nondependent/dependent ratio between the optimum global positive end-expiratory pressure-inspiratory-CT and optimum-selective positive end-expiratory pressure-inspiratory-CT (2.8 ± 1.1 vs 0.6 ± 0.3; p = 0.01); and 4) less tidal recruitment ( p = 0.049). Conclusions: After maximum lung recruitment, lateral decubitus and differential lung ventilation enabled the titration of optimum-selective positive end-expiratory pressure values for the dependent and the nondependent lungs, made possible the application of an optimized regional open lung approach, promoted better aeration distribution, and minimized lung tissue inhomogeneities.